On nonlocal three-point boundary value problems of Duffing equation with mixed nonlinear forcing terms - Alsaedi, Ahmed; Aqlan, Mohammed HA (Boundary value problems, 2011)
In this paper, we investigate the existence and approximation of the solutions of a nonlinear nonlocal three-point boundary value problem involving the forced Duffing equation with mixed nonlinearities. Our main tool of the study is the generalized quasilinearization method due to Lakshmikantham. Some illustrative examples are also presented. Mathematics Subject Classification (2000): 34B10, 34B15.